PENERAPAN BLENDED LEARNING PADA TPQ RAUDHATUL ‘ULUM MEMASUKI ERA NORMAL BARU MASYARAKAT - Setyawan Wibisono; Wiwien Hadikurniawati; Endang Lestariningsih; Aji Supriyanto (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Taman Pendidikan Al-Qur’an (TPQ) Raudhatul 'Ulum is a community-based religious education institution established at the initiative of Jamaah Musholla Al Iman aimed at kindergarten and elementary school age children in the area of ​​RW 01, Kelurahan Manyaran, West Semarang District, Semarang City. The learning system at TPQ Raudhatul 'Ulum is done face-to-face every afternoon. In mid-March 2020 when the Covid-19 pandemic began to hit Indonesia, face-to-face learning had to be replaced with online learning. When the pandemic is under control, a new normal era will be implemented with learning using a blended learning system. The application of blended learning is to simultaneously apply three learning strategies that are combined into one form of learning, namely: online learning, face-to-face learning and independent learning. The application of the blended learning strategy creates problems for TPQ Raudhatul 'Ulum teachers, namely: teachers are not yet skilled in online learning management as a basis for blended learning, teachers are not yet skilled in the use of software for the preparation of online learning media, teachers are not yet skilled in preparing materials and assignments in independent learning, teachers are not yet skilled in the use of online learning support tools. The priority solution in this PKM is the implementation of training and assistance in blended learning-based learning management. Teachers are also given software training for the preparation of online learning media in accordance with the concept of blended learning. Training on the preparation of materials and assignments in independent learning was also carried out, as well as training in the use of online learning support tools.